Beragam Jalan Menjadi Salih: Model Dakwah Kelas Menengah Muslim Indonesia - Ahmad Khoirul Fata; Oki Setiana Dewi (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
This paper examines the religious phenomenon of the contemporary Indonesian Muslim middle class. The study is focused on the da'wah model that takes place and is of interest to urban Muslims. With descriptive analysis where datas were collected from the field, the authors found several forms of dakwah that had been prevailing in the middle class of Indonesian Muslims: 1) Model seminars and short courses. This model is at least represented by the Paramadina’s Religious Studies Club (KKA) and FAST; 2) The general study model through television and new internet-based media. Among the popular dais who made use of this route were Aa Gym, Khalid Basalamah, and Felix Siauw; 3) Community recitation model. This last model is usually a follow-up to the second model, where they want a more in-depth study so that they form a limited separate study group. This paper also shows that that the Muslim middle class is actively seeking a form of Islam that suits their needs. They take advantage of information technology for that purpose. And their Islamic passion is not a form of conservatism or radicalism, but rather an effort to become more devout Muslims.